Relationship Between TB Treatment Phase and Knowledge of MDR TB with TB Patient’s Compliance - I Dewa Ayu Made Made Yuni (Jurnal Berkala Epidemiologi, 2016)
Indonesia is the country with the second-largest contributor to pulmonary tuberculosis (TB) cases in the world after India. Among new cases, an estimated 3.3% are multidrug-resistant tuberculosis (MDR-TB), a rate that has remained unchanged in recent years. This study aims to analyze the relationship between the treatment phase and knowledge about MDR-TB with the treatment compliance of TB patients. The research was conducted at the pulmonary tuberculosis polyclinic from the Public health center (PHC) of Perak Timur in April - May 2016. The method used was observational analytic cross-sectional design. Sampling using Simple Random Sampling. Questionnaires were given to 59 TB patients who received anti-tuberculosis drugs (OAT). The variables studied were patient characteristics (age, sex, education, and occupation), treatment phase, knowledge of MDR-TB, and patient medication adherence. The results of the study with the chi-square test showed that there was a relationship between the treatment phases (p = 0.03; PR = 1.593) and knowledge of MDR-TB (p = 0.039; PR = 1.164) with the treatment compliance of TB patients. The conclusion of the study is that there is a relationship between the treatment phase and knowledge of MDR-TB with TB patient treatment adherence, so it is recommended that PHC staff provide education about MDR-TB through direct counseling to drug supervisor officers and patients and attaching educational posters, and continue to provide motivation to patients to remain do treatment regularly and thoroughly.